Tests to determine relative values of alcohol, gasoline, and kerosene as fuel for internal combustion engines - Orr, Burton Sylvester; Tilbury, S. Ray (My University, 1907)
Introduction: The object of this series of tests was to determine the relative value of gasoline, denatured alcohol, and kerosene as fuel for an internal combustion engine designed and built for the use of gasoline. The fuels were tested under practically the same conditions, the only changes made in the engine were such that were necessary for obtaining the greatest brake horse power possible. The first or trial tests were made with a strap brake but it was soon found that this was not suitable for engines or motors above five horse power. We also found that oil was the best for cooling a brake of this type. After proving that the strap brake was insufficient, a wooden Prony brake was constructed and used throughout the remaining tests. With this brake a constant supply of water proved better for cooling, but there was a small amount of chattering which could not be avoided on account of the engine being of the four cycle type. The engine used was a ten horse power Witte Gasoline using the "hammer break" type of igniter. The fuel tank was placed on the wall above the engine so the supply did not depend on the pump. This tank was fitted with a gage glass so the amount of fuel at the start could be marked and at the end of the test, the overflow was put back and the tank filled to the point marked at the start. The amount required to fill the tank to the starting point, after putting back the overflow, was what the engine had used during the test. The cooling water for the cylinder...
Citation: Orr, Burton Sylvester and Tilbury, S. Ray. Tests to determine relative values of alcohol, gasoline, and kerosene as fuel for internal combustion engines. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Internal Combustion Engine; Fuel for Combustion Engine; Engine Testing; Engineering; Material Science; Theses